PERSEPSI PESERTA DIDIK TERHADAP PENERAPAN LMS SCHOOLOGY DALAM PEMBELAJARAN IPA - SRI HASTUTI VIRGIANTI PULUKADANG; MERY NAPITUPULU; DAUD K WALANDA; AFADIL AFADIL (Jurnal Ilmu Pendidikan Indonesia, 2020)
The development of science and science and technology is always followed by the development of teachers and students in the field of education. Science and technology has a great influence on life and the environment. Students' understanding of science and its ability to apply it in life. Through this principle, students not only learn to listen to the teacher's explanation, but students can find out the real way of learning. The integration of technology, in this case the Schoology learning management system (LMS), is expected to help students understand science. This study aims to determine students' perceptions of the application of LMS Schoology in the seventh grade students of SMP Gamaliel Palu. The results of quantitative descriptive analysis showed that students gave a positive response to the progress of science by using Schoology.